STUDI TENTANG CORPORATE GOVERNANCE DAN PENGARUHNYA TERHADAP KINERJA KEUANGAN BANK YANG TERCATAT DI BURSA EFEK INDONESIA - Suharmanto - Suharmanto (Politeknik Negeri Semarang, 2015)
This study aims to analyze the effect of goodcorporate governance on bank financialperformance listed in IDX. Constructs weredeveloped this study, External CorporateGovernance proxy for RegulatoryCompliance, as measured by the CapitalAdequacy Ratio (CAR), Internal CorporateGovernance- Manager proxy for SensitivityCompensation-Performance, InternalCorporate Governance-owner proxy withVariance coefficient Net Interest Margin(NIM), Financial Performance proxied byReturn on Assets (ROA). The population usedin this study were all commercial banks listedon the Stock Exchange from 2009-2013. Thedata used in this study in the form of annualfinancial statements obtained from thePublications Indonesia Stock Exchange(IDX). After passing through the stagepurposive sample, the samples were used by30 (thirty) banks. The method of analysis usedin this study is the analysis of panel dataregression. With the model specification testuse Random Effect Model (REM). coefficientof determination (R2), test hypothesis with asignificance level of 5%. The results showedthat the variable External CorporateGovernance proxied by the Capital AdequacyRatio (CAR) and a significant effect on ROAand Internal Corporate Governance-Managerproxy for Sensitivity Compensation-Performance not effect on ROA. While theInternal Corporate Governance-owners proxywith Variance coefficient Net Interest Margin(NIM), has a significant effect on ROA. Oftwo significant variables, variables InternalCorporate Governance-Owner proxied by thecoefficient of variance NIM has a greatereffect on financial performance (ROA).